Future Expectations and Internet Addiction Among Adolescents: The Roles of Intolerance of Uncertainty and Perceived Social Support - Du, Gang; Lyu, Houchao (Frontiers in Psychiatry, 2021)
Internet addiction is a common and challenging problem among adolescents. Previous studies have shown that future time orientation is an important protective factor against internet addiction. In this study, the mediating effect of intolerance of uncertainty and the moderating role of perceived social support were examined on the association between future expectations, regarded as the "prospective life course" perspective of future time orientation, and internet addiction among adolescents. A total of 1006 Chinese adolescents (54% male and 46% female; Mage = 15.42 years, SD = 1.32) recruited from middle schools completed questionnaires. Results indicated that future expectations were significantly negatively associated with internet addiction, and the link was mediated by intolerance to uncertainty in adolescents. Further, the latent moderated structural equation showed that perceived social support moderated the association between future expectations and intolerance of uncertainty. The association was significant only for adolescents with a higher level of perceived social support. The findings of this study provide specific guidelines for how to prevent adolescent internet addiction.